2011
DOI: 10.1074/jbc.m111.222679
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and Pancreatic Exocrine Dysfunction Due to Mutations in the Carboxyl Ester Lipase Gene-Maturity Onset Diabetes of the Young (CEL-MODY)

Abstract: CEL-maturity onset diabetes of the young (MODY), diabetes with pancreatic lipomatosis and exocrine dysfunction, is due to dominant frameshift mutations in the acinar cell carboxyl ester lipase gene (CEL). As Cel knock-out mice do not express the phenotype and the mutant protein has an altered and intrinsically disordered tandem repeat domain, we hypothesized that the disease mechanism might involve a negative effect of the mutant protein. In silico analysis showed that the pI of the tandem repeat was markedly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
113
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 85 publications
(120 citation statements)
references
References 49 publications
4
113
1
2
Order By: Relevance
“…Pathway-We previously reported that secretion of both CEL-WT and CEL-MUT from HEK293 cells occurs at similar rates (26). However, the microscopic data described above indicated that the two proteins display clearly distinct intracellular distributions (Fig.…”
Section: Cel-wt and Cel-mut Co-distribute With Markers Of The Early Smentioning
confidence: 76%
See 4 more Smart Citations
“…Pathway-We previously reported that secretion of both CEL-WT and CEL-MUT from HEK293 cells occurs at similar rates (26). However, the microscopic data described above indicated that the two proteins display clearly distinct intracellular distributions (Fig.…”
Section: Cel-wt and Cel-mut Co-distribute With Markers Of The Early Smentioning
confidence: 76%
“…Moreover, in vivo excreted CEL-MUT can be detected in pancreatic juice from the patients. Our findings led to the suggestion that CEL-MODY is a protein misfolding disease in which the CEL-MUT protein forms aggregates leading to the stimulation of the unfolded protein response (26).…”
mentioning
confidence: 82%
See 3 more Smart Citations